How is gender-specific vulnerability understood and assessed in SAPCC? - Madhuri, (Frontiers in Sociology, 2025)
Climate action is only truly possible by incorporating gender-specific vulnerabilities and adaptation measures. National Action Plans for Climate Change (NAPCC) and State Action Plans for Climate Change (SAPCCs) seek to mainstream vulnerable communities, such as women, at the national and state levels. It is uncertain how these plans incorporate gender-specific vulnerabilities and equip women with adequate measures to deal with climate impacts. This paper employs content analysis method to analyze a total of 33 action plans for climate change (APCC); out of 33 APCCs, 28 are SAPCCs, five are union territories action plans for climate change mainly through three themes- gendered vulnerability, gender-disaggregated data, gender capacity-building policies, and adaptation measures. The research delves into the nexus of gender-focused climate action and adaptation policy within India’s climate policy. Based on the findings, the study classifies states as highly gender-responsive, moderately gender-responsive, and gender-blind. The gender responsiveness of the state is different due to differences in women’s agricultural participation, political commitment to gender equality, and cultural norms regarding gender roles. The research identifies a necessity of enhancing gender mainstreaming in climate policy to ensure that women’s vulnerability is effectively addressed.